Utilization of Citrus Peel Waste Into Anti-Mosquito Spray Preparations as An Alternative to Malaria Prevention - Firdaus Adwi Pangga; Hajar Hikmah Fahbulan; Indah Sayekthi Dwi Wardani; Rosita I. Dehi; Fitriah A. Iriani (International Journal of Integrative Sciences, 2024)
Malaria is one of the infectious diseases that is still a health problem for the community. Anopheles sp mosquitoes  are vectors for spreading malaria caused by plasmodium sp. parasites. The content of citric acid in oranges, makes this fruit has a sour taste that gives a fresh aroma. Essential oils found in orange peels can generally be used as anti-mosquito spray deodorizers. Orange peels can repel mosquitoes because mosquitoes do not like the smell of fragrances. Essential oils contain gologan organic compounds terpenes and terpenoids that are oil-soluble (lipophilic). This study aims to determine the use of citrus peel waste into mosquito repellent spray preparations as an alternative to malaria prevention with variations of active substances infusion of orange peel F1 (20%), F2 (40%). The sample used in this study was an infusion of citrus fruit peel (Citrus Sinensis L).  The results of organoleptis test research have a distinctive aroma of sweet orange fruit peel, yellow color and liquid form. While the average pH for all is to have a pH of 5, and for homogeneity tests all three homogeneous formulas are seen in macroscopic and microscopic ways. Test mosquito protection power, in this study the average results obtained for F1 is 43%, and F2 63% for mosquito protection standards is 90%